Unsteady mixed convection near the forward stagnation point of a two-dimensional symmetric body - Nazar, Roslinda; Amin, Norsarahaida; Pop, Ioan (Elsevier Ltd., 2003)
The unsteady mixed convection boundary layer flow near the forward stagnation point of a two-dimensional symmetric body resulting from an impulsive motion of the free stream velocity and by sudden increase in the surface temperature. The partial differential equations governing the flow and heat transfer have been solved numerically using Keller-box method. It is shown that there is a smooth transition from the unsteady initial flow (short time) to the final steady state flow(large time). It is also found that for the steady flow case that are dual solutions when the flow is opposing